Perkembangan Umkm Sebelum Dan Sesudah Memperoleh Siup Di Perumahan Bougenville Lestari Kecamatan Alam Barajo Jambi - Aisyah Yasmi; Miftah; Ahmad Syahrizal (JOURNAL SAINS STUDENT RESEARCH, 2023)
In this era of globalization, business development is occurring very rapidly. The growth of various types of business is happening everywhere, one of which is MSMEs. The government is currently prioritizing the development of MSMEs because the number of MSMEs in Indonesia is quite large compared to large businesses. This research aims to find out how much influence the SIUP or Business Legality has on the development of MSMEs in Bougenville Lestari Housing, Alam Barajo District, Jambi City, before and after they obtain the SIUP. This research uses qualitative methods with data collection techniques through observation. Documentation and direct interviews with sources. The number of MSMEs studied was 19 MSMEs that had obtained a SIUP. Of the 19 MSME owners, on average, they stated that whether or not they owned a SIUP did not affect the development of their business, especially in the sales sector. However, with this SIUP, MSMEs have many opportunities to further develop their business, both in terms of marketing and production. Based on the results of this research, it can be concluded that the development of MSMEs before and after obtaining a SIUP in Bougenville Lestari Housing, Alam Barajo subdistrict, Jambi City tends to not develop or be stuck even though they have obtained a SIUP or Business Lrgality.